اختيار المقطع العرضي للرافعة الجسرية وحيدة الجائز ذات المقطع العلبي بوزن أصغري وباستخدام الحاسوب - هولا, عيسى (Latakia University Journal -Engineering Sciences Series, 2019)
1- النوعية: تستخدم الروافع الجسرية في المصانع والورشات. نقوم في البداية بتحديد نوعية الرافعة حسب حمولتها Q فإذا كانت الحمولة فإننا نختار الرافعة الجسرية وحيدة الجائز وفي حال كون الحمولة نختار الرافعة ثنائية الجائز. 2- الدراسة النظرية: لقد تم اختيار المقطع العلبي للجائز الرئيسي للرافعة وقمنا بإعداد الدراسة النظرية لهذا المقطع، من حيث سماكة الصفائح الأفقية والشاقولية المكونة له، وأبعاده الطولية والعرضية وحصلنا على تابع رياضي يربط العلاقة بينها وبين الحمولة الخارجية استناداً إلى شرط المتانة. 3- الخوارزمية: لقد تم إنشاء خوارزمية لحساب المقطع العرضي استناداً إلى القساوة ثم تدفق وفق المتانة والاستقرار وقد حددت جميع العلاقات والتوابع لهذه الخوارزمية. 4- البرنامج: تم برمجة الخوارزمية المشار إليها أعلاه باستخدام لغة (دلفي)، وهكذا بإعطاء حمولة الرافعة ومجازها وسرعة حركتها تعطينا استناداً إلى الخوارزمية المذكورة أعلاه وباستخدام الحاسوب سماكة الصفائح المكونة للمقطع وأبعاده وكذلك عدد صفائح الدعم الشاقولية ضمن المجاز، والمسافة بينها ووزن الجائز الرئيسي والإجهادات العظمى في المقطع الخطر. 5- النتيجة: إننا نستطيع أن نوفر في كمية المعدن المستخدم في تصنيع الرافعة مع المحافظة على المتانة والقساوة والاستقرار المطلوبين. 1- Kind: we use overhead crane in factories and workshops. At first, we select the kind of the crane according to capacity (Q), if we select the single girder overhead crane and if we select double girder overhead crane. 2- Theoretical Analysis: we select the box-type section for the main beam of the crane and prepare the theoretical analysis of this section which explains the relation between the thickness of the vertical and horizontal plates and the dimensions of this section and the load on the beam according to the theory of strength. The outcome was a mathematical function from which we can derive the minimum weight of this section according to the conditions of strength, stability and rigidity. 3- Algorithm: Through this paper we offer algorithm calculation for the section of the single girder overhead crane according to the rigidity and compliance with the conditions of strength and satiability. All the formulae and functions that were included in the algorithm have been determined. 4- Program: the already mentioned algorithm was programmed by the use of (Delphi) computer language and thus, by giving the crane load, the span and the speed, it give us, based on the already mentioned algorithm and the use of computer the thickness of the horizontal and vertical plates section, the dimensions of the section, quantity of the diaphragms and the distance between them in the span of the crane, the weight of the crane and the stress in the dangerous section. 5- Conclusion: as a result, we can economize the amount of the metal when manufacturing the crane, saving the strength, the stability and the rigidity of the crane.